Doubling the Rate of Improvement of Energy Efficiency - Sinton, Jonathan; Sarkar, Ashok; Jaques, Ivan; Bushueva, Irina (World Bank, Washington, DC, 2014)
Over the 20-year period between 1990 and 2010, strong demo¬graphic and economic growth around the world caused global primary energy consumption to grow at a compound annual rate of 2 percent annually. Even so, falling energy intensity (the amount of energy used to produce a unit of economic output) meant that global energy demand in 2010 was more than 20 percent lower than it otherwise would have been. The energy intensity of the global economy fell during the period from 10.2 to 7.9 megajoules per U.S. dollar (2005 dollars at PPP). The reduction was driven by cumulative improvements in energy efficiency, partially offset by growth in activity, resulting in energy savings of nearly 2,300 exajoules over the 20-year period. Doubling the rate of improvement of global energy efficiency is one of the three complementary objectives of the Sustainable Energy for All (SE4ALL) initiative. Launched in the UN General Assembly in September 2012 and co-chaired by the president of the World Bank Group and the UN Secretary-General, SE4ALL calls on governments, businesses, and civil society to address urgent energy challenges, including energy efficiency, by 2030.